The Effect of Augmented Reality Based Learning Strategy on EFL Students' Vocabulary Mastery - Siregar, Dinda Salsabilah; Syahputri, Diani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of an Augmented Reality (AR)-based learning strategy on EFL students’ vocabulary mastery. Conducted at Thammasat Wittaya School, Thailand, the research involved 25 eighth-grade students in the 2024/2025 academic year, divided into experimental and control groups using a quasi-experimental design. The experimental group received vocabulary instruction through AR visuals and collaborative discussions, while the control group was taught using conventional methods. Data were collected using pre-tests and post-tests and analyzed using paired and independent t-tests. The findings revealed a significant improvement in vocabulary scores and student motivation in the experimental group compared to the control group (p 0.001). These results suggest that integrating AR-based strategies in EFL classrooms can effectively enhance vocabulary acquisition and learner engagement.